Outcomes of abdominoperineal resection for management of anal cancer in HIV-positive patients: a national case review. Issue 1 (December 2016) - Leeds, Ira; Alturki, Hasan; Canner, Joseph; Schneider, Eric; Efron, Jonathan; Wick, Elizabeth; Gearhart, Susan; Safar, Bashar; Fang, Sandy
Abstract Background The incidence of anal cancer in human immunodeficiency virus (HIV)-positive individuals is increasing, and how co-infection affects outcomes is not fully understood. This study sought to describe the current outcome disparities between anal cancer patients with and without HIV undergoing abdominoperineal resection (APR). Methods A retrospective review of all US patients diagnosed with anal squamous cell carcinoma, undergoing an APR, was performed. Cases were identified using a weighted derivative of the Healthcare Utilization Project's National Inpatient Sample (2000–2011). Patients greater than 60 years old were excluded after finding a skewed population distribution between those with and without HIV infection. Multivariable logistic regression and generalized linear modeling analysis examined factors associated with postoperative outcomes and cost. Perioperative complications, in-hospital mortality, length of hospital stay, and hospital costs were compared for those undergoing APR with and without HIV infection. Results A total of 1725 patients diagnosed with anal squamous cell cancer undergoing APR were identified, of whom 308 (17.9 %) were HIV-positive. HIV-positive patients were younger than HIV-negative patients undergoing APR for anal cancer (median age 47 years old versus 51 years old, p < 0.001) and were more likely to be male (95.1 versus 30.6 %, p < 0.001). Postoperative hemorrhage was more frequent in the HIV-positive group (5.1 versus 1.5 %, p = 0.05). Mortality was low in both groups (0 % in HIV-positive versus 1.49 % in HIV-negative, p = 0.355), and length of stay (LOS) (10+ days; 75th percentile of patient data) was similar (36.9 % with HIV versus 29.8 % without HIV, p = 0.262). Greater hospitalization costs were associated with patients who experienced a complication. However, there was no difference in hospitalization costs seen between HIV-positive and HIV-negative patients (p = 0.66). Conclusions HIV status is not associated with worse postoperative recovery after APR for anal cancer as measured by length of stay or hospitalization cost. Further study may support APRs to be used more aggressively in HIV-positive patients with anal cancer.